Print vs Digital Reading Comprehension in EFL - Pardede, Parlindungan (JET (Journal of English Teaching), 2019)
Printed texts have long been used as the prime medium of learning to read and reading to learn. However, the ubiquity of technology has emerged digital texts, and the accelerating influx of digital texts requires new comprehension skills and strategies. This article reviews and synthesizes current ideas and research findings on digital reading in EFL context to provide a more solid theoretical basis for digital texts use in reading comprehension programs. Discussion in this article begins with the comparison of the nature of conventional or print reading versus digital reading and the characteristics of printed texts versus digital texts. After that, the discussion proceeds to the findings of relevant studies concerning the effect of digital reading to comprehension, students and instructors' perception of digital texts, and strategies for reading digital texts.